Experimental study on failure process of arch dam based on acoustic emission technique. (March 2019) - Wang, Shouguang; Liu, Yaoru; Zhou, Haowen; Zhang, Ying; Wu, Zheshu; Yang, Qiang
Abstract: Geomechanical model test is an important way to analyze the safety of high arch dams. The traditional monitored displacements and stresses are difficult to interpret the internal failure process of dams and foundations. Acoustic emission(AE) technique was used in the geomechanical model test of arch dam to analyze its internal failure. AE 2D planar locating technology for arch dams and signal parameter analysis method were studied and applied to an arch dam geomechanical model test. The failure process of the dam body and foundation was revealed. The left dam heel of the arch dam model cracked first, continuing to expand to higher elevation along the left abutment with the increase of overload times, and the horizontal crack penetration leaded to the ultimate failure of the dam body. Safety factors for initial crack, nonlinear deformation and ultimate bearing capacity of the arch dam model had been clearly obtained based on AE technique. The results of AE analysis coincided well with the actual failure condition. So it is confirmed that AE technique is effective for geomechanical model test, and it has a bright prospect to be used in situ test of arch dam. Highlights: Acoustic emission technique is used in the geomechanical model test of arch dam. A planar location algorithm for arch dam is established with multiple regression. The failure process of arch dam model is obtained based on AE technique. The three overload safety factors of the arch dam model were obtained.